Palliative fenestration for a symptomatic subcarinal bronchogenic cyst by the prone position approach - Nakamura, Toru (J Surg Case Rep, 2019)
A complete excision is the most reliable therapy for bronchogenic cysts (BC) but is often accompanied by technical difficulties due to severe adhesions. An 83-year-old-woman with poorly controlled diabetes noted worsening upper abdominal pain after meals and paroxysmal atrial fibrillation. Magnetic resonance imaging revealed a cystic mass in the subcarinal region, and she underwent a thoracoscopic prone position surgery. The cyst wall was found to have strictly adhered to the adjacent organs, and the lesion was not amenable to a complete excision. We performed a fenestration of the cyst wall with the aspiration of an yellowish mucus content. After opening the cavity wide enough, the remnant luminal epithelium was ablated by electrocautery. Her clinical symptoms disappeared immediately after the surgery without any surgical morbidity. A prone-position thoracoscopic palliative fenestration is a feasible option for a symptomatic subcarinal BC.